Specific Features of the Education of Muslim Children in the Czech Republic - Kliment, Pavel (Wydawnictwo Naukowe UAM, 2016)
The paper tackles the requirements of the Muslim children’s parents on a change of the form of their teaching in various types of schools in the Czech Republic and the way in which the schools cope with these requirements.
Cechy szczególne kształcenia dzieci muzułmańskich w Republice Czeskiej
Keywords: Muslim; Muslim Children; education of Muslim Children